REKAYASA PERANGKAT LUNAK TOKO ONLINE PADA BATIK FARIZ PEKALONGAN (Information Technology and Telematics, 2013)
Abstraksi   Internet is a technology that has advanced rapidly. Akhirya up in this era (digital era) no one missed without hearing or reading the word Shop Online in various sales information. Online store is a transaction in which the actors perform transactions over the Internet. Is an achievable goal is to create an online store application that can be accessed by anyone at any time using the internet, by leveraging advances in Internet technology that aims to provide convenience to consumers, so as to attract customers, so buy the product that is in Batik Fariz Pekalongan. The results achieved in this study is the presence of online stores in Batik Pekaongan Fariz also be easier for consumers to make purchases batik regardless of time and place, as well as providing kemudahkan to consumers to obtain the latest product information from Fariz Batik Pekalongan quickly easily and accurately . Kata Kunci :  Toko Online, Konsumen, E-Commerce